PENGEMBANGAN MEDIA E-LEARNING BERBASIS TWITTER PADA MATERI BIOLOGI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN - MARYAMAH, MARYAMAH; ROVIATI, EVI (Jurnal Ilmu Pendidikan Indonesia, 2021)
This study aims to determine whether Twitter-based e-learning media can be developed as a media for teaching biology on the structure and function of plant tissue. This research method is research and development. The research sample was teenage smartphone users in Walahar Village, Cirebon Regency. The results showed that e-learning based on twitter can be used and developed as a medium of teaching materials on the structure and function of plant networks